2023
DOI: 10.1590/0034-7167-2023-0091pt
|View full text |Cite
|
Sign up to set email alerts
|

Concordância com conteúdos de desinformação relacionados à COVID-19 em idosos falantes do português: estudo internacional

Abstract: RESUMO Objetivos: avaliar a concordância com conteúdos de desinformação relacionados à COVID-19 entre pessoas com 50 anos ou mais de idade, falantes do português. Métodos: estudo descritivo e analítico com 1.214 idosos nascidos em países de língua portuguesa. A coleta de dados ocorreu por meio da mineração de informações online para reconhecimento de conteúdos de desinformação e COVID-19, e aplicação de questionário estruturado. Resultados: a concordância com conteúdos de desinformação foi de 65,2%. Residir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…This issue is particularly acute in Brazil, a country with more than 200 million people facing numerous challenges, such as political division, unequal access to healthcare, and socioeconomic disparities that may shape attitudes toward immunization. For instance, a study exploring racial disparities revealed that Black men in Brazil were less likely to have received the COVID-19 vaccine [13][14][15][16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This issue is particularly acute in Brazil, a country with more than 200 million people facing numerous challenges, such as political division, unequal access to healthcare, and socioeconomic disparities that may shape attitudes toward immunization. For instance, a study exploring racial disparities revealed that Black men in Brazil were less likely to have received the COVID-19 vaccine [13][14][15][16].…”
Section: Literature Reviewmentioning
confidence: 99%